Improved Stability of Organic Photovotlaic Devices With FeCl3 Intercalated Graphene Electrodes - Walsh, Kieran K.; Murphy, Conor; Russo, Saverio; Craciun, Monica F. (Frontiers in Electronics, 2021)
In this paper, we present the first organic photovoltaic (OPV) devices fabricated with FeCl3 intercalated few layer graphene (i-FLG) electrodes. i-FLG electrodes were first fabricated and characterized by electrical and spectroscopic means, showing enhanced conductive properties compared to pristine graphene. These electrodes were then used in the fabrication of OPV devices and tested against devices made with commercially available ITO electrodes. Both types of device achieved similar efficiencies, while the i-FLG based device exhibited superior charge transport properties due to the increase in work function characterizing i-FLG. Both types of device underwent a stability study using both periodic and continuous illumination measurements, which revealed i-FLG based OPVs to be significantly more stable than those based on Indium Tin Oxide (ITO). These improvements are expected to translate to increased device lifetimes and a greater total energy payback from i-FLG based photovoltaic devices. These results highlight the potential benefits of using intercalated graphene materials as an alternative to ITO in photovoltaic devices.